2019
DOI: 10.21685/1680-0826-2019-13-2-4
|View full text |Cite
|
Sign up to set email alerts
|

The first record of Paracineta irregularis (Ciliophora, Suctorea) as epibiont on Rhombognathus halacarid mite (Acari, Halacaridae) from the Sea of Marmara, Turkey

Abstract: This study presents the data on the new finding of suctorian ciliate Paracineta irregularis on halacarid mite Rhombognathus sp. from the Sea of Marmara, Turkey. Diagnostic characters of P. irregularis such as contractility of tentacles and position of macronucleus are emended based on the material collected from the new locality. The mode of the species reproduction by semi-circumvaginative exogemmic budding is described for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Second, we selected a case study to test explicitly the latter assumption. We used halacarid marine mites as model organisms because they are common in seagrasses such as P. oceanica (Mari & Morselli, 1990;Zupo, 1993;Durucan, 2018;Durucan & Boyacı, 2018;Durucan & Levent, 2019), yet the habitat preferences of the species associated with this . CC-BY-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we selected a case study to test explicitly the latter assumption. We used halacarid marine mites as model organisms because they are common in seagrasses such as P. oceanica (Mari & Morselli, 1990;Zupo, 1993;Durucan, 2018;Durucan & Boyacı, 2018;Durucan & Levent, 2019), yet the habitat preferences of the species associated with this . CC-BY-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we selected a case study to test explicitly the latter assumption. We used halacarid marine mites as model organisms because they are common in seagrasses such as P. oceanica (Mari & Morselli, 1990;Zupo, 1993;Durucan, 2018;Durucan & Boyacı, 2018;Durucan & Levent, 2019), yet the habitat preferences of the species associated with this plant have never been explicitly investigated. This case study, therefore, provides a point of comparison with the better studied copepods and nematodes (Novak, 1989;Mascart et al, 2013)…”
Section: Introductionmentioning
confidence: 99%
“…Marine and fresh water mites have been identified as hosts of suctorian ciliates which may be commensals, ecto -or endoparasites. They are common epibionts on marine and freshwater invertebrates such as copepods, cladocerans, nematodes, kinorhynchs, halacarid and hydrachnid mites (Chatterjee, Nanajkar, Dovgal, Sergeeva, Bhave, 2019;Durucan, Boyacı, 2016;Durucan, Artüz, Dovgal, 2019). In Turkey, the first taxonomic study on marine suctorians was done by Durucan and Boyacı (2019) who reported Praethecacineta halacari (Schulz, 1933) on Copidognathus venustus Bartsch, 1977 from Levantine Sea (Antalya).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we expected that different halacarid species would prefer different habitats within an individual of P. oceanica. Marine mites are common inhabitants of seagrasses such as P. oceanica (Durucan, 2018(Durucan, , 2021Durucan et al, 2019;Durucan & Boyacı, 2018;Mari & Morselli, 1990;Zupo, 1993), yet the habitat preferences of the species associated with P. oceanica have never been explicitly investigated. We expected that this case study would provide evidence of such preferences to complement information available in the literature from the better studied copepods and nematodes (Mascart et al, 2013;Novak, 1989).…”
mentioning
confidence: 99%